Comprehensive analysis of healthy eating in students of C.E.I. Alfonso Ugarte y Vernal in Huancavelica - Palacio Anaya, Max Jefferson (2024)
Healthy eating is an essential pillar for the physical, mental, and emotional development of adolescents, as a balanced diet directly influences their concentration, academic performance, and overall well-being. In this context, the purpose of this research was to analyze students' eating habits and implement strategies aimed at strengthening the adoption of healthy eating practices that contribute to improving their school performance and quality of life. The study was conducted using a descriptive approach, with documentary analysis and a non-experimental design, at the Alfonso Ugarte y Vernal Educational Institution, located in the district of Pampas-Huancavelica (3,265.58 meters above sea level). The results show that more than half of the students recognize the importance of healthy eating for their academic performance and future health; however, before the intervention, there was limited knowledge about the consequences of an inadequate diet. Following the implementation of workshops, surveys, and educational activities, a moderate improvement was observed in the understanding and appreciation of healthy foods, accompanied by an increase in the willingness to change unfavorable habits. The strategies implemented, based on nutrition education, the use of teaching materials, and the promotion of healthy eating environments, contributed to raising awareness, autonomy, and student commitment, creating an environment that favors the development of sustainable habits and promotes the overall well-being of schoolchildren. The results highlight the need to incorporate food education as a cross-cutting component of the school curriculum.